Women’s Language Used By Characters In “Brave” Movie - Ananda Sinta Ramadina; Ni Luh Nyoman Seri Malini; Ni Luh Putu Krisnawati (CV. Ulil Albab Corp, 2022)
Abstract: The title of this research is women’s language used by the characters in Brave movie. It aims to analyze the types of female language used by the characters in Brave movie. The data source is taken from the Brave movie script. The data was collected by reading the movie script and choosing which part contains women’s language in movie